Core Competencies of the Certified Pediatric Doctor of Chiropractic: Results of a Delphi Consensus Process. (April 2016) - Hewitt, Elise; Hestbaek, Lise; Pohlman, Katherine A.
An outline of the minimum core competencies expected from a certified pediatric doctor of chiropractic was developed using a Delphi consensus process. The initial set of seed statements and substatements was modeled on competency documents used by organizations that oversee chiropractic and medical education. These statements were distributed to the Delphi panel, reaching consensus when 80% of the panelists approved each segment. The panel consisted of 23 specialists in chiropractic pediatrics (14 females) from across the broad spectrum of the chiropractic profession. Sixty-one percent of panelists had postgraduate pediatric certifications or degrees, 39% had additional graduate degrees, and 74% were faculty at a chiropractic institution and/or in a postgraduate pediatrics program. The panel were initially given 10 statements with related substatements formulated by the study's steering committee. On all 3 rounds of the Delphi process the panelists reached consensus; however, multiple rounds occurred to incorporate the valuable qualitative feedback received.